(3QSGdI NeGQ Hf MHjT GdSdeGfi GdYcGhis - (3NeGQ Hf MHjT GdSdeGfj GdYcGhjs
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf CeG HYO jG NeGQ Ef cGf GSec ai GdCUd MGQJ EHdjS dGjZQc EegGdc ai GdOfjG s
(3BNQgG (B:s
(3afbdJgG bJd GdcdGH hCbhGe GNQjf ai GdYPGH MJi jhO hGdLGdjI hge UGZQhf hPdc HbhI ehdGfG Ld PcQg dGTQjc dg hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B13s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds